Engineering Optics - Iizuka, Keigo; SpringerLink (Online service) (New York, NY : Springer New York, 2008)
Engineering Optics is a book for students who want to apply their knowledge of optics to engineering problems, as well as for engineering students who want to acquire the basic principles of optics. It covers such important topics as optical signal processing, holography, tomography, holographic radars, fiber optical communication, electro- and acousto-optic devices, and integrated optics (including optical bistability). As a basis for understanding these topics, the first few chapters give easy-to-follow explanations of diffraction theory, Fourier transforms, and geometrical optics. Practical examples, such as the video disk, the Fresnel zone plate, and many more, appear throughout the text, together with numerous solved exercises. There is an entirely new section in this updated edition on 3-D imaging.
History of Optics -- Mathematics Used for Expressing Waves -- Basic Theory of Diffraction -- Practical Examples of Diffraction Theory -- Geometrical Optics -- Lenses -- The Fast Fourier Transform (FFT) -- Holography -- Laboratory Procedures for Fabricating Holograms -- Analysis of the Optical System in the Spatial Frequency Domain -- Optical Signal Processing -- Applications of Microwave Holography -- Fiber Optical Communication -- Electro and Accousto Optics -- Integrated Optics -- 3D Imaging.
Keywords: Physics; Optics; Electrodynamics; Lasers; Photonics; Optoelectronics; Plasmons (Physics).; Microwaves; Optical engineering; Electronics; Microelectronics; Physics; Optics and Electrodynamics; Optics, Optoelectronics, Plasmonics and Optical Devices; Laser Technology, Photonics; Microwaves, RF and Optical Engineering; Electronics and Microelectronics, Instrumentation; Signal, Image and Speech Processing; Electronic books